Effect of Chitosan on Meat Preservation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
The effect of chitosan as preservative on the qualities of meat including microbiological, chemical, sensory and color qualities were examined In liquid medium chitosan 0.01% inhibited the growth of some spoilage and pathogenic bacteria such as Bacillus subtilis, Escherichia coli, Pseudomonas fragi and Staphylococcus aureus. At 0.1% concentration it also inhibited the growth of meat starter cultures, Lactoba¬cillus plantarum, Pediococcus Pentosaceus and Micro-coccus varians. In meat, during incubation at 30°C for 48 hours or storage at 4°C for 10 days, chitosan inhib¬ited the growth of spoilage bacteria, reduced lipid oxi¬dation, putrefaction and resulted in better sensory test. Chitosan also had a good effect on the development of red color of meat during storage.